Current developments of eco-friendly organic field-effect transistors: from molecular engineering of organic semiconductors to greener device processing. Issue 34 (6th April 2023) - Lee, Gyeong Seok; Kwon, Hyeok-jin; An, Tae Kyu; Kim, Yun-Hi
Abstract : Molecular engineering of organic semiconductors for environmental friendliness or processing engineering. Abstract : Replacing environmentally damaging toxic halogenated/aromatic hydrocarbon organic solvents commonly used in solution-processed organic field-effect transistors with more sustainable green solvents has in recent years become a subject of various studies. In the current review, we summarize the properties of solvents used to process organic semiconductors and relate these properties to the toxicities of the solvents. And then, the research efforts to avoid using toxic organic solvents are reviewed, in particular the efforts involving molecular engineering of organic semiconductors achieved by introducing solubilizing side chains or substituents into the backbone and with synthetic strategies to asymmetrically deform the structure of the organic semiconductors and random copolymerization, as well as efforts involving the use of miniemulsion-based nanoparticles to process organic semiconductors.